2015
DOI: 10.3389/fneur.2015.00069
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Concussions in Adolescent Athletes – Translating Clinical and Experimental Research into Perspectives on Rehabilitation Strategies

Abstract: Sports-related concussions are particularly common during adolescence, a time when even mild brain injuries may disrupt ongoing brain maturation and result in long-term complications. A recent focus on the consequences of repetitive concussions among professional athletes has prompted the development of several new experimental models in rodents, as well as the revision of guidelines for best management of sports concussions. Here, we consider the utility of rodent models to understand the functional consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 187 publications
(288 reference statements)
1
17
0
Order By: Relevance
“…Furthermore, although the design of this study limits the interpretation of the differences between the single and RmTBI groups (i.e., different recovery times before the onset of behavioral testing – discussed further below), there was a trend in the beam testing data indicating that the RmTBI rats had more slips and falls 24 h after the third mTBI compared to 24 h after the first mTBI, suggesting a cumulative effect with the repeated injuries. Although there is some preliminary human evidence that adolescents may experience worse mTBI outcomes than young adults (see Semple et al, 2015),44 many of the changes in the current study are similar to those observed in adult rats given repeated mTBI. For example, adult male rats administered repeated mild fluid percussion injuries had cumulative and persisting cognitive deficits, motor abnormalities, anxiety‐like behavior, and depression 45, 46.…”
Section: Discussionsupporting
confidence: 61%
“…Furthermore, although the design of this study limits the interpretation of the differences between the single and RmTBI groups (i.e., different recovery times before the onset of behavioral testing – discussed further below), there was a trend in the beam testing data indicating that the RmTBI rats had more slips and falls 24 h after the third mTBI compared to 24 h after the first mTBI, suggesting a cumulative effect with the repeated injuries. Although there is some preliminary human evidence that adolescents may experience worse mTBI outcomes than young adults (see Semple et al, 2015),44 many of the changes in the current study are similar to those observed in adult rats given repeated mTBI. For example, adult male rats administered repeated mild fluid percussion injuries had cumulative and persisting cognitive deficits, motor abnormalities, anxiety‐like behavior, and depression 45, 46.…”
Section: Discussionsupporting
confidence: 61%
“…Specifically, more information regarding reasons for lengthier recovery times with non-NP consults would be beneficial. The number of prolonged concussions (those that take longer than 2 weeks to recover) represents a small percentage of total concussions, but is an important subset of cases due to implications for serious injury and prolonged recovery times (Semple et al, 2015). The median time to the last CNT was longer in this cohort than that reported in the literature, as was the number of cases taking longer than 2 weeks.…”
Section: Discussionmentioning
confidence: 65%
“…In addition, in vitro models reflecting brain cell–specific changes that occur following trauma could be a promising strategy for high‐throughput screening of emerging therapies. Furthermore, repetitive TBI has recently received a lot of attention in sports and the military, and animal models have been developed to study this type of injury (Kane et al, ; Semple et al, ; McAteer et al, ; Ojo et al, ; Winston et al, ). Future preclinical studies focused on the effect of repetitive TBI on PTH‐associated symptoms would provide much needed insight on how the brain's pain‐processing regions adapt to repeated injury.…”
Section: Discussionmentioning
confidence: 99%